European inventory on validation of non-formal and informal learning 2014 : country report Germany - Annen, Silvia [Verfasser]; Bretschneider, Markus [Verfasser] (My University, 2014)
"There is currently no overall national approach to validation of non-formal and informal learning in Germany, but good progress has been made during the last three years. Within the formal system of education, which already contains elements for the validation of non-formal and informal learning, bottom-up and top-down approaches complement each other. A new approach is the Vocational Qualifications Assessment Law (Gesetz über die Feststellung der Gleichwertigkeit von Berufsqualifikationen. The implementation of the German Qualifications Framework for Lifelong Learning (DQR) on 1 May 2013 is another measure which might support the greater use of validation. Being developed as a comprehensive framework, the DQR is open to encompass not only formal qualifications but also non-formally and informally acquired competences. Besides these operational approaches, there are other 'conceptual preliminary studies' for the recognition of non-formal and informal learning. In 2013, a working group on validation was set up by the Federal Ministry of Education and Research. It aims at identifying topics and options for activities, as well as agreements for practical steps. For example, part of the work is to compile a compendium of studies in the field of competence development and informal learning for the purpose of spreading knowledge across Germany." (authors' abstract; BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 2.1 Deutschland; Non-formales Lernen; Informelles Lernen; Anerkennung; Deutscher Qualifikationsrahmen; Anerkennungsgesetz; Bundesrepublik Deutschland